2010
DOI: 10.1007/s00280-010-1297-x
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative chemotherapy for colorectal cancer liver metastases: an update of recent clinical trials

Abstract: setting the association of chemotherapy with bevacizumab and cetuximab is particularly promising in improving resectability rate. In particular, K-RAS is a molecular response predictive factor that could be particularly useful in selecting the best treatment option in pts with unresectable liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Neoadjuvant chemotherapy prior to hepatectomy in patients with resectable CRLM may increase the resectability of liver lesions, treat occult metastasis, improve progression-free survival, allow for testing of the chemosensitivity of the cancer in situ, help to determine the appropriateness of further treatments, and identify progressive disease that contraindicates immediate surgery [14]. An Italian study of 25 patients with primarily resectable CRLM treated with neoadjuvant chemotherapy found that 18 (72%) responded to chemotherapy, and the 5-year overall survival was 71%, which indicates that the response to chemotherapy is likely to be a significant prognostic factor affecting overall survival after radical hepatic resection [15].…”
Section: Discussionmentioning
confidence: 99%
“…Neoadjuvant chemotherapy prior to hepatectomy in patients with resectable CRLM may increase the resectability of liver lesions, treat occult metastasis, improve progression-free survival, allow for testing of the chemosensitivity of the cancer in situ, help to determine the appropriateness of further treatments, and identify progressive disease that contraindicates immediate surgery [14]. An Italian study of 25 patients with primarily resectable CRLM treated with neoadjuvant chemotherapy found that 18 (72%) responded to chemotherapy, and the 5-year overall survival was 71%, which indicates that the response to chemotherapy is likely to be a significant prognostic factor affecting overall survival after radical hepatic resection [15].…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative chemotherapy reduces the size of hepatic metastases, therefore resulting in the conversion of initially unresectable disease to potentially resectable disease, and hence increasing the likelihood that the metastatic tumor will be curatively resected 5-7. In addition, neoadjuvant treatment may also treat micrometastases which are not detected by imaging studies 7.…”
mentioning
confidence: 99%
“…Preoperative chemotherapy reduces the size of hepatic metastases, therefore resulting in the conversion of initially unresectable disease to potentially resectable disease, and hence increasing the likelihood that the metastatic tumor will be curatively resected 5-7. In addition, neoadjuvant treatment may also treat micrometastases which are not detected by imaging studies 7. The most popular regimens are those that combine fluoropyrimidines with irinotecan or oxaliplatin, including the 5-fluorouracil (5-FU) and oxaliplatin (FOLFOX) and 5-FU, oxaliplatin and irinotecan (FOLFIRI) regimens 5-11…”
mentioning
confidence: 99%
“…For example, the UK National Institute for Health and Clinical Excellence (NICE) does not recommend the use of bevacizumab in mCRC and cetuximab has only recently been recommended for restricted use in the UK [19–21]. Since there is some evidence that adding an mAb to cytotoxic chemotherapy may increase resection rates compared with the use of cytotoxic chemotherapy alone [22], this may partially explain the relatively lower rates of surgical procedures for metastases and curative purposes in the UK.…”
Section: Discussionmentioning
confidence: 99%